Optimization of Daylight Factor Distribution Using Standard Deviations Based on Shifting Window Position - Yose Rizal; Imam Robandi; Eko Mulyanto Yuniarno (Jurnal Ilmiah Kursor, 2020)
Natural lighting is an important factor that affects the comfort of building users. Natural lighting in a room requires a window area of ​​at least 1/6 of the floor area. This study was conducted to obtain the distribution of Daylight Factor (DF) as a natural lighting factor during the day in the room, based on the shift in the position of the window on the wall. The distribution of lighting entering the depth of the room through window openings is a tool to compare the best window position in the spread of illumination with DF calculations based on Sky Component (SC). Shifting the window position will be analyzed by Standard Deviation (S) and Mean (μ) based on the DF distribution. Optimizations of the DF distribution on the window position shifts if it has the largest DF mean value and the smallest DF variant value. The results of the study in a simple room showed that the optimal DF distribution was at the window position in the middle and the mean value was 2.59%. The relationship of shifting window position and DF distribution can be useful for architects to determine the function of a room in architectural design.